Is Greed a Double-Edged Sword? The Roles of the Need for Social Status and Perceived Distributive Justice in the Relationship Between Greed and Job Performance - Zhu, Yiming; Sun, Xiaomin; Liu, Sijia; Xue, Gang (Frontiers in Psychology, 2019)
Greed is one of the most common features of human nature, and it has recently attracted increasing research interest. The aims of this paper are to provide one of the first empirical investigations of the effects of greed on job performance and to explore the mediating role of the need for social status and perceived distributive justice. Using a working sample (N=315) from China, the current study found that greed promoted both task and contextual performance through the intermediary effect of the need for social status. At the same time, greed inhibited both types of performance through perceived distributive justice. These results confirmed our hypothesis that greed is a double-edged sword with opposite effects on one’s performance. The findings suggest that organizations should both address greedy employees’ social status concerns and ensure that they are treated fairly so that organizations can fully utilize the talents of greedy people and channel their energy in a beneficial direction.